BUBULAK LAKI-LAKI ATAU PEREMPUAN? KAJIAN TENTANG PEREMPUAN DALAM PENGELOLAAN AGROFORESTRI BUBULAK DI KUNINGAN, JAWA BARAT - Dede Tresna Wiyanti; Mutia Latifah; Hardian Eko Nurseto; Budiawati Supangkat (Universitas Padjadjaran, 2022)
This research aims to describe women’s roles in managing the bubulak. Bubulak is one of the agricultural land near the forest. This research was conducted in Cisukadana Village, Kadugede Districts, Kuningan District, West Java. Cisukadana Village was chosen because women farmers in this village must adapt themselves with the changing of labor division in agriculture because of the absent of their husbands). The husbands have to work outtside the village as non-agriculture workers. The method that used in this research is qualitative with case study approach. Data collection is done by collecting secondary and primary data. The primary data collected by observations and interviews.The results showed the majority work in bubulak are done by women. Women managing bubulak by themselves or sometimes employing male farm laborer for some types of work, the husbands will help the work when they were home. Women choose type of plant that do not need intensive care/maintenance, so they can also work on another type of agricultural land and finished their domestic tasks. Based on the result, the lack of men worker and the dominant of women in manage the bubulak from the maintaining the crops, harvesting, and proccessing the harvest before consume, and also all of the knowledge about the technology, made bubulak as a women’s bubulak.